Survei Motivasi Belajar Siswa Kelas X Dalam Mata Pelajaran PJOK SMA Keberbakatan Olahraga Bahteramas Sulawesi Tenggara - Jumiati, Basman, Resky Ana Abadi (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
The aim of this research is to determine the learning motivation of Class Based on the results of the research and discussion above, the results of research at the Bahteramas Sports Gifted School, Southeast Sulawesi on July 25 2024. Research has been carried out on the learning motivation of class person. This research is used to carry out measurements with the aim of producing accurate data." The data to be obtained in this research was collected using a questionnaire. So researchers can conclude that physical education learning has undergone a change from online to offline (face-to-face) learning, thus affecting students' learning motivation. If we look at the learning motivation of students taking physical education and sports lessons, it is in the medium category with an average score of 75 and the percentage level of 100% of students in the sample is 2% in the low category, 42% in the very high category, 29% in the medium category and 15% in the high category.